Treatment of acute lymphoblastic leukemia with protocol Hongkong–Indonesia Acute Lymphoblastic Leukemia 97 - Johannes Bondan Lukito (Paediatrica Indonesiana, 2007)
Background The HK-Ina ALL 97 study protocol is based on theTherapy Study ALL-BFM 95 protocol. Basically, this protocolstratifies the patients into three groups, i.e. standard risk for lowrisk group (SR), intermediate risk (IR), and high risk (HR) group,and the treatment is directed according to the risk groups.Objectives To investigate the overall treatment result of childhoodALL in Indonesia and to stratify patients according to biological,clinical criteria, and molecular study that identify the standardand high risk patients with greater precision.Methods Twenty patients entered in this study; 10 SR, 6 IR and 4HR groups. Induction phase for SR group consisted of four drugs(phase I’a) for five weeks and three drugs combination (phase I’b)for four weeks. Consolidation phase consisted of four doses of mini-HD MTX (2 gram/m 2 ) (protocol M’), reinduction phase useddexamethasone for seven weeks, and maintenance phase consistedof 6 MP and MTX. Boys, who were at higher risk of relapse, weregiven pulse dexamethasone and vincristine. Induction phase for IRwas the same as SR, but four doses of daunorubicin were given to IRgroup (Ia). Consolidation phase included four doses HDMTX (5gram/m 2 ). Phase Ib and Protocol II was the same as SR group. Pulsedexamethasone and vincristine was given to all patients. Inductionphase for HR group will be the same as IR group. This followed bythree blocks of very intensive treatment. Two reinduction phasesand maintenance was the same as SR and IR groups.Results Nineteen of 20 patients achieved complete remission (CR).The patient who could not stand was a 10 years old boy with initialWBC 612X10 9 /L, T-lineage marrow. He died 5 months since the initialdiagnosis after treated with HDMTX with dominant CD33 and sepsis.Conclusion The EFS in this study is 95% for the observation of 5months through five years and two months. It is still expected thatthe result fall off in the subsequent year, but it is also expected to becomparable to 70-80%. The very intensive and toxic program forHR group, may improve the EFS, but may also cause secondaryAML in the earlier time.